2017
DOI: 10.1186/s12917-017-1112-6
|View full text |Cite
|
Sign up to set email alerts
|

Geospatial and temporal associations of Getah virus circulation among pigs and horses around the perimeter of outbreaks in Japanese racehorses in 2014 and 2015

Abstract: BackgroundWe studied a recent epizootic of Getah virus infection among pigs in the southern part of Ibaraki Prefecture and the northern part of Chiba Prefecture, Japan, focusing on its possible association with outbreaks in racehorses in 2014 and 2015. The genomic sequence of a Getah virus strain from an infected pig was analyzed to evaluate the degree of identity with the strains from horses.ResultsSera were collected from pigs from September to December 2012 to 2015 in south Ibaraki (380 pigs in 29 batches),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Researchers had continuously detected the GETV neutralizing antibodies in pigs and horses in Ibaraki and Chiba of Japan (Bannai et al 2017). The results showed that in south Ibaraki, the seroprevalence of neutralizing antibody in pigs ranged from 0% to 1.6% in 2012-2013, but it was 28.8% and 65.0% in 2014 and 2015, respectively; In north Chiba, it ranged from 0% to 1.6% in 2010-2012, and was 14.1%, 17.8%, and 48.0% in 2013-2015, respectively.…”
Section: Fig 1 Serological Survey Of Getv In Domestic Animalsmentioning
confidence: 99%
“…Researchers had continuously detected the GETV neutralizing antibodies in pigs and horses in Ibaraki and Chiba of Japan (Bannai et al 2017). The results showed that in south Ibaraki, the seroprevalence of neutralizing antibody in pigs ranged from 0% to 1.6% in 2012-2013, but it was 28.8% and 65.0% in 2014 and 2015, respectively; In north Chiba, it ranged from 0% to 1.6% in 2010-2012, and was 14.1%, 17.8%, and 48.0% in 2013-2015, respectively.…”
Section: Fig 1 Serological Survey Of Getv In Domestic Animalsmentioning
confidence: 99%
“…Subsequently, outbreaks of GETV infection have occurred among horses in 1979, 1983, 2014 and 2015 in Japan (Bannai et al., ; Nemoto et al., ; Sentsui & Kono, ; Sugiura et al., ) and in 1990 in India (Brown & Timoney, ). In pigs, sporadic cases of GETV infection were reported in the 1980s in Japan (Shibata, Hatano, Nishimura, Suzuki, & Inaba, ; Yago, Hagiwara, Kawamura, & Narita, ); a recent seroepizootiologic investigation found GETV circulating in south Ibaraki and north Chiba in Japan, and this circulation was concomitant with the outbreaks in racehorses (Bannai et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…An epidemic occurred at the same location in 2016. In addition, Getah viruses were isolated from mosquitoes in 2012 ( 7 ) and pigs in 2015 ( 8 ). Here, we read the complete genome sequences of the strains isolated from horses in 2016 and compared them with those of the strains recently isolated from horses, pigs, and mosquitoes.…”
Section: Genome Announcementmentioning
confidence: 99%
“…Three strains (16-I-599, 16-I-674, and 16-I-676) from blood samples that were positive for Getah virus by reverse transcription-PCR ( 9 ) were successfully isolated in Vero cells ( 10 ). The genomes of the three strains were sequenced using the Ion Personal Genome Machine system (Thermo Fisher Scientific, Waltham, MA, USA), as described previously ( 8 ). The raw signal data were analyzed by using Torrent Suite version 5.0.5, and 14-I-605-C1 (GenBank accession no.…”
Section: Genome Announcementmentioning
confidence: 99%
See 1 more Smart Citation